Development of a health care systems curriculum - Pruitt Z (Advances in Medical Education and Practice, 2017)
Zachary Pruitt,1 Rahul Mhaskar,2 Bryan G Kane,3 Robert D Barraco,4 Deborah J DeWaay,2 Alex M Rosenau,3 Kristin A Bresnan,5 Marna Rayl Greenberg3 1Department of Health Policy and Management, College of Public Health, Morsani College of Medicine, University of South Florida, Tampa, FL, 2Department of Internal Medicine, Morsani College of Medicine, University of South Florida, Tampa, FL, 3Department of Emergency Medicine, Morsani College of Medicine, University of South Florida, Lehigh Valley Campus, Allentown, PA, 4Department of Surgery, Morsani College of Medicine, University of South Florida, Lehigh Valley Campus, Allentown, PA, 5Department of Family Medicine, Morsani College of Medicine, University of South Florida, Lehigh Valley Campus, Allentown, PA, USA Background: There is currently no gold standard for delivery of systems-based practice in medical education, and it is challenging to incorporate into medical education. Health systems competence requires physicians to understand patient care within the broader health care system and is vital to improving the quality of care clinicians provide. We describe a health systems curriculum that utilizes problem-based learning across 4 years of systems-based practice medical education at a single institution.Methods: This case study describes the application of a problem-based learning approach to system-based practice medical education. A series of behavioral statements, called entrustable professional activities, was created to assess student health system competence. Student evaluation of course curriculum design, delivery, and assessment was provided through web-based surveys.Results: To meet competency standards for system-based practice, a health systems curriculum was developed and delivered across 4 years of medical school training. Each of the health system lectures and problem-based learning activities are described herein. The majority of first and second year medical students stated they gained working knowledge of health systems by engaging in these sessions. The majority of the 2016 graduating students (88.24%) felt that the course content, overall, prepared them for their career.Conclusion: A health systems curriculum in undergraduate medical education using a problem-based learning approach is feasible. The majority of students learning health systems curriculum through this format reported being prepared to improve individual patient care and optimize the health system’s value (better care and health for lower cost). Keywords: health systems, undergraduate medical, education